Nigeria Since Independence - Hill, J. author. aut Link
XIII, 173 p.
Keywords: This book analyses the political and ethnical tensions that characterize Nigeria, which derive both from colonial and contemporary conflicts. It points out three major factors why Nigeria has not yet collapsed like many other African states: ethnic power sharing amongst the political elite, the military with its national outlook, and oil wealth.